Dopaminergic neurons establish a distinctive axonal arbor with a majority of non‐synaptic terminals. Issue 8 (28th July 2021) - Ducrot, Charles; Bourque, Marie‐Josée; Delmas, Constantin V. L.; Racine, Anne‐Sophie; Guadarrama Bello, Dainelys; Delignat‐Lavaud, Benoît; Domenic Lycas, Matthew; Fallon, Aurélie; Michaud‐Tardif, Charlotte; Burke Nanni, Samuel; Herborg, Freja; Gether, Ulrik; et al.
Abstract: Chemical neurotransmission typically occurs through synapses. Previous ultrastructural examinations of monoamine neuron axon terminals often failed to identify a pre‐ and postsynaptic coupling, leading to the concept of "volume" transmission. Whether this results from intrinsic properties of these neurons remains undefined. We find that dopaminergic neurons in vitro establish a distinctive axonal arbor compared to glutamatergic or GABAergic neurons in both size and propensity of terminals to avoid direct contact with target neurons. While most dopaminergic varicosities are active and contain exocytosis proteins like synaptotagmin 1, only 20% of these are synaptic. The active zone protein bassoon was found to be enriched in dopaminergic terminals that are in proximity to a target cell. Finally, we found that the proteins neurexin‐1α SS4− and neuroligin‐1 A+B play a critical role in the formation of synapses by dopamine (DA) neurons. Our findings suggest that DA neurons are endowed with a distinctive developmental connectivity program.